Variations in different preceding crops on the soil environment, bacterial community richness and diversity of tobacco-planting soil - Liu, Ming; Xue, Rujun; Wang, Dexun; Hu, Yanxia; Gu, Kaiyuan; Yang, Liu; Zhao, Jie; Guan, Shuyue; Su, Jiaen; Jiang, Yonglei (Frontiers in Microbiology, 2024)
Tobacco (Nicotiana tabacum L.) is a major cash crop, and soil quality played a significant role in the yield and quality of tobacco. Most farmers cultivate tobacco in rotation with other crops to improve the soil characteristics. However, the effects of different previous crops on the soil's nutrient status and bacterial community for tobacco cultivation still need to be determined. Three treatments were assessed in this study, i.e., tobacco-planting soil without treatment (CK), soil with barley previously cultivated (T1), and soil with rapeseed previously cultivated (T2). The soil physical and chemical properties and the 16S rRNA gene sequence diversity of the bacterial community were analyzed. The effects of different crops on the physical and chemical